2012
DOI: 10.1103/physrevb.86.125102
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic dipole and electric quadrupole transitions in the trivalent lanthanide series: Calculated emission rates and oscillator strengths

Abstract: Given growing interest in optical-frequency magnetic dipole transitions, we use intermediate coupling calculations to identify strong magnetic dipole emission lines that are well suited for experimental study. The energy levels for all trivalent lanthanide ions in the 4f n configuration are calculated using a detailed free ion Hamiltonian, including electrostatic and spin-orbit terms as well as two-body, three-body, spin-spin, spin-other-orbit, and electrostatically correlated spin-orbit interactions. These fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
164
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(184 citation statements)
references
References 81 publications
(146 reference statements)
16
164
3
1
Order By: Relevance
“…However, we note that, for these particular transitions, the cancellation factor as defined by Cowan [22] is very small (<0.05), indicating that the corresponding decay rates might be affected by larger uncertainties in our calculations. For all of the other forbidden lines reported in Table 3, an accuracy of about 10% can reasonably be estimated for our computed gA-values in view of their excellent agreement with the results obtained using a completely independent theoretical method [23]. …”
Section: Magnetic Dipole and Electric Quadrupole Transitionssupporting
confidence: 81%
See 2 more Smart Citations
“…However, we note that, for these particular transitions, the cancellation factor as defined by Cowan [22] is very small (<0.05), indicating that the corresponding decay rates might be affected by larger uncertainties in our calculations. For all of the other forbidden lines reported in Table 3, an accuracy of about 10% can reasonably be estimated for our computed gA-values in view of their excellent agreement with the results obtained using a completely independent theoretical method [23]. …”
Section: Magnetic Dipole and Electric Quadrupole Transitionssupporting
confidence: 81%
“…Transition probabilities obtained using our physical model A for the most intense magnetic dipole (M1) and electric quadrupole (E2) lines are reported in Table 3. They are compared with the results recently published by Dodson and Zia [23] who calculated radiative transition probabilities for some M1 and E2 Tm IV lines using a detailed free ion Hamiltonian including electrostatic and spin-orbit terms as well as two-body, three-body, spin-spin, spin-other-orbit and electrostatically correlated spin-orbit interactions. When looking at Table 3, we can note that their results are generally in good agreement (within a few percent) with our transition probabilities, if we except some E2 transitions located at 3038.774, 3847.249, 4264.491, 4437.432, 4721.408, 5759.349, 6401.911 and 7967.695 Å for which larger discrepancies are observed.…”
Section: Magnetic Dipole and Electric Quadrupole Transitionsmentioning
confidence: 87%
See 1 more Smart Citation
“…For this reason, radiative properties of such forbidden lines within the 4f 3 configurations were also computed in the present work. Transition probabilities for the most intense magnetic dipole (M1) and electric quadrupole (E2) lines are reported in table 5 where they are compared to the data recently published by Dodson and Zia (2012). These latter authors reported radiative transition probabilities for some M1 and E2 Nd IV lines using a detailed free ion Hamiltonian including electrostatic and spin-orbit terms as well as two-body, three-body, spin-spin, spin-other-orbit and electrostatically correlated spin-orbit interactions.…”
Section: Forbidden Transitionsmentioning
confidence: 99%
“…1) and the values of the reduced matrix elements for particular electric-dipole transitions from [21] have been used. For the sake of completeness, generally weak magnetic-dipole transitions have been taken into account, with the values of the oscillator strengths and radiative probabilities from [26]. Due to similarity of the absorption spectra of TWPLa:Pr and TWPLu:Pr glasses (see Fig.…”
Section: Resultsmentioning
confidence: 99%